Diagnosis and Management of Anemia in The Elderly - Pratiwi Anggraini; Theophany Margareta Kurniawan; Ima Arum Lestarini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Anemia is one of the hematological disorders that can contribute to increased morbidity and mortality in the elderly because it can be a risk factor for various other diseases so that accurate diagnosis and appropriate management are needed. This literature review aims to provide related information, so that proper diagnosis and management for anemia in the elderly can be carried out to reduce morbidity and mortality rates. In this literature review we conducted a search on the PubMed database using the search keyword